The research of diesel injection pumps performance on biofuel with different viscosity rate - Labeckas, Gvidonas; Slavinskas, Stasys (Transport, 2002)
The main purpose of this research work is to determine the influence of fuel viscosity on the performance of diesel injection pumps of different design in order to clear up some of the changes in fuel feeding when running them in accordance with governor characteristics on the biofuel derived from vegetable oil. The given fuel temperature/viscosity relationships and dependencies of fuel feeding on its viscosity applying biofi1el on different injection pumps can be practically useful for adjusting them for the work on bio-diesel. According to the analysis of the got results the in-line diesel injection pumps are more suitable for their adaptation for the work on bio-diesel. In this case only small adjustments of biofuel feeding rate are needed.First Published Online: 19 Dec 2011